Effect of gas flow rate and deposition pressure toward the crystallographic and surface morphology of semi-polar (112̅2) gallium nitride grown by MOCVD / Ooi Chong Seng - Ooi , Chong Seng (2022)
V/III ratio and pressure is frequently varied to study the metalorganic chemical vapor deposition (MOCVD) growth parameters effect on semi-polar (112̅2) gallium nitride epitaxy (GaN) growth on m-plane (101̅0) sapphire substrate. In the first study, V/III ratio is fixed at 118 while varying the Trimethylgallium (TMG) (33.6, 59, 84.3 and 100 sccm) and ammonia (NH3) (0.4, 0.7, 1.0 and 1.3 SLM) flow rate, respectively. Varying gas flow rate implies different growth rate is induced. Different GaN film with different surface morphologies was produced and their crystal quality was determined. High-resolution Xray diffraction (HR-XRD) analysis shows that low gas flow enhanced the GaN crystal quality with lowest FWHM values of 576 and 1656 arcsecs at [11 ̅̅̅̅23] and [11̅00], respectively. Field-emission scanning electron microscope (FESEM) also verified that 2D GaN morphology is produced. Whereas high gas flow exhibits low crystal quality together with the distribution of 3D islands on the surface. Atomic force microscopy (AFM) micrographs show different arrowhead elongation length produced at a different flow rate. The presented results suggest that low gas flow rate with low growth rate is necessary to obtain a flat semi-polar (112̅2) GaN layer. In the second study, the first experiment is repeated by growing on AlN nucleation layer at fixed V/III ratio of 1300 with lower TMA and NH3 flow rate. There was not much difference in the HR-XRD analysis between the first and second series. The phase and the X-ray rocking curve (XRC) analysis consistently show that the crystal quality improved when TMG and NH3 gas flow rate is lowered. However, the FESEM results showed that there were less 3D islands formed compared to the first series when GaN grown on aluminum nitride (AlN) nucleation layer with lower gas flow rate. In contrast, the AFM analysis showed quite similar surface roughness with the first series when compared with each TMG gas flow rate, respectively. The third study involved the variation of reactor pressure (40, 70 and 100 kPa) on GaN epitaxial layer. It has been found out that highest reactor pressure of 100 kPa effectively reduced the dislocations and stacking faults with lowest FWHM value of 416 and 857 arcsecs at [11 ̅̅̅̅23] and [11̅00], respectively. However, higher growth pressure resulted in very rough surface morphology and larger surface grain size which led to 3D growth mode. The surface roughening mechanism for both gas flow rate and pressure variation are also explained using the adatom surface diffusion relation